Shifted nonlocal Kundu type equations: Soliton solutions - Aslı Pekcan (Partial Differential Equations in Applied Mathematics, 2022)
We study the shifted nonlocal reductions of the integrable coupled Kundu type system. We then consider particular cases of this system; namely Chen–Lee–Liu, Gerdjikov–Ivanov, and Kaup–Newell systems. We obtain one- and two-soliton solutions of these systems and their shifted nonlocal reductions by the Hirota bilinear method. We present particular examples for one- and two-soliton solutions of the reduced shifted nonlocal Chen–Lee–Liu, Gerdjikov–Ivanov, and Kaup–Newell equations.